2023
DOI: 10.1186/s12877-022-03719-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frailty, geriatric syndromes, and comorbidity on mortality and quality of life in older adults with HIV

Abstract: Background To understand the effects of frailty, geriatric syndromes, and comorbidity on quality of life and mortality in older adults with HIV (OAWH). Methods Cross-sectional study of the FUNCFRAIL multicenter cohort. The setting was outpatient HIV-Clinic. OAWH, 50 year or over were included. We recorded sociodemographic data, HIV infection-related data, comorbidity, frailty, geriatric syndromes (depression, cognitive impairment, falls and malnutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…While the presence of multiple NCDs is generally burdensome for PLWH and negatively impact their QoL and mortality risk ( 12 ), our study found that having >2 NCDs increased QoL in the ‘past, present, and future activities’ domain. This odd result suggests a potential influence of specialized clinic care ( 20 ), frequent visits, and proactive healthcare-seeking behavior among OPWH with co-morbidities in our setting, warranting further exploration.…”
Section: Discussionmentioning
confidence: 51%
“…While the presence of multiple NCDs is generally burdensome for PLWH and negatively impact their QoL and mortality risk ( 12 ), our study found that having >2 NCDs increased QoL in the ‘past, present, and future activities’ domain. This odd result suggests a potential influence of specialized clinic care ( 20 ), frequent visits, and proactive healthcare-seeking behavior among OPWH with co-morbidities in our setting, warranting further exploration.…”
Section: Discussionmentioning
confidence: 51%
“…On the other hand, more than half of the non-robust participants in our study became robust after the 12-week MEP which makes the results particularly significant. The interest and scientific evidence on frailty and HIV have grown markedly over the past 10 years, but the bulk of the published material has focused on the prevalence of frailty in different countries and settings ( 20 ), on its ability to predict adverse health events ( 21 ), on its relationship with biomarkers ( 22 , 23 ), and/or with other health conditions ( 24 ), nevertheless, until now, no evidence has been available concerning treatment. Some scientific societies recommend frailty screening in people over 50 years of age with HIV ( 25 ), however, health professionals had no evidence-based intervention to offer until now beyond extrapolating on the interventions that have proven effective in the overall population ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed the association between worse HQoL and frailty among PWH, as reported previously. 20 , 35 , 36 The ACTG SF-21 instrument used measured eight HQoL domains. 27 Other studies have also shown associations of frailty with the domains of HQoL evaluated here, including neurocognitive impairment association with increased risk of frailty in an observational cohort evaluating aging and HIV, the ACTG A5322 study.…”
Section: Discussionmentioning
confidence: 99%